2018
DOI: 10.1093/jac/dky062
|View full text |Cite
|
Sign up to set email alerts
|

High virological suppression regardless of the genotypic susceptibility score after switching to a dolutegravir-based regimen: week 48 results in an observational cohort

Abstract: This observational cohort study showed a high level of virological suppression maintenance in the first year following the switch to a dolutegravir-based regimen, even in patients with GSS ≤2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…To the best of my knowledge, there is no set factor for weighting different INSTIs. More recent studies have, similar to our results, found DTG-based ART to be robust even with GSS < 1.5 (149). However, in both studies, participants with GSS scores in effect close to DTG monotherapy were few.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of my knowledge, there is no set factor for weighting different INSTIs. More recent studies have, similar to our results, found DTG-based ART to be robust even with GSS < 1.5 (149). However, in both studies, participants with GSS scores in effect close to DTG monotherapy were few.…”
Section: Discussionsupporting
confidence: 90%
“…The ART-PRO study reported that no participants experienced virological failure when integrase-inhibitor-naïve, virologically suppressed patients were switched to dual therapy with dolutegravir plus lamivudine, even though 21 of the 41 participants had lamivudine resistance mutations in historical plasma genotypes( 24 ). Similar findings were reported in switch studies evaluating lamivudine and dolutegravir dual therapy( 25 ) and dolutegravir with companion drugs to which resistance was documented( 26 ). The efficacy of TLD in our study, despite resistance to one or both of tenofovir and lamivudine in 89% of our participants, may be attributable to the crippling effect that NRTI mutations have on viral fitness, resulting in residual antiviral activity( 13 ).…”
Section: Discussionsupporting
confidence: 84%
“…Also, NRTI resistance may prevent the emergence of DTG resistance [12]. Other trials and observational studies have also found DTG, or the similar drug bictegravir, combined with fewer than one active NRTI, to be effective, though typically as a switch strategy in the setting of virologic suppression, which makes the current study findings even more notable [13][14][15].…”
mentioning
confidence: 61%